Immediate impacts of air pollution on the performance of football players - Li, J.; Sun, S.; Ho, M. S. (Journal of Sports Economics, 2024)
Understanding the immediate impacts of air pollution is crucial, especially as non-health outcomes like player productivity are covert. This paper focuses on investigating the causal relationship between air pollution and player productivity, which is theoretically established by the health consequences of air pollution and the Grossman health production function. The dataset used comprises over 20,000 observations from 1,440 matches in the Chinese Football Association Super League from 2014 to 2019. The IV estimation results show that a 1% increase in air pollution results in a reduction of 0.101% in the number of passes, which is five times larger than the OLS estimation. Heterogeneity results suggest that possessing an advantage (physical fitness, technical skills, or playing at home) contributes to mitigating the adverse effects of air pollution. This study underscores the critical role of clean air in enabling football players to achieve high productivity in the game.